Empirical Study of Entrepreneurial Attitude and Entrepreneurial Intentions towards Entrepreneurship among PG Diploma Students in Chennai District - J. Prahbu (European Alliance for Innovation (EAI), 2021)
The present short article is an attempt that has been made to examine the students' attitude and intentions in the direction of Entrepreneurship in Chennai City. Entrepreneurial Personality type consists of the human features, capabilities, motives, mindsets, and also worths that form the individual person's experiences as well as actions. Entrepreneurial intentions are likewise taken into consideration as personal alignments which might cause venture developments. Hence, personality traits create the psychological and also behavioral procedures of people. Entrepreneurship is area relevance has elevated multifold over the last couple of decades around the world and also in the last number of years in India. Entrepreneurship has actually come to be a daily buzzword. Policymakers, economists, academics and even college students are discussing it.